Response of cactus pear (Opuntia ficus-indica Mill.) to boron and farmyard manure application under arid soils conditions in Kutch, Gujarat - Naorem, Anandkumar; Patel, Sachin; Hassan, Sawsan; Louhaichi, Mounir; Sarker, Ashutosh (International Society for Horticultural Science, 2022)
As livestock is an important component of livelihoods in the arid regions of Kutch in Gujarat, India, smallholder farmers have difficulties in cultivating fodder crops during the driest seasons of the year. Water scarcity in arid regions can negatively affect feed intake, digestion and body weight of animals. The cactus pear [Opuntia ficus-indica (L.) Mill.] has gained attention in Kutch because it serves as a good green fodder. To understand the plant growth response of Opuntia-ficus indica Mill. to inorganic fertilizers and organic manures, a field experiment was conducted with 12 treatment combinations, three levels of farmyard manure and four levels of boron and compared in a randomized complete block design with three replications over two years. The results showed substantial increases in cactus pear growth after applying farmyard manure during the first year and second year of planting. Boron contributed to significant changes in cactus pear growth only during the second year of planting. The integrated application of both farmyard manure and boron can enhance cactus pear growth during the second year of planting